Adapting to Change in Nepal’s Hospitality and Tourism Industry - Chaudhary, Manoj Kumar (Nepalese Journal of Hospitality and Tourism Management, 2026)
This is volume 7 issue 1 of the Nepalese Journal of Hospitality and Tourism Management. The eight papers in this issue show how Nepal’s tourism and hospitality industries are changing. These articles provide a mix of research and practical information covering topics from high-end hotels to low-cost accommodations. The articles discuss leadership, employee behavior, rules, service quality and what visitors think showing how complex the tourism and hospitality industries are in Nepal. The research articles look at big-picture issues for luxury hotels and everyday problems for budget accommodations.